A knowledge-based model on quality management system compliance assessment for maritime higher education institutions. Issue 2 (4th May 2021) - Pehlivan, Davut; Cicek, Kadir
ABSTRACT: A quality management system is an essential and mandatory instrument for maritime higher education institutions mandated by the International Convention on Standards of Training, Certification, and Watchkeeping for Seafarers. To design an effective quality management system, it is strongly recommended to take the most comprehensive model of the quality system such as ISO 9001 quality management system. This paper proposes a knowledge-based model for assessing the compliance level of the quality management system of maritime higher education institutions with respect to ISO 9001:2015 to provide meaningful information to design an effective quality management system, to identify potential gaps and required improvement points in the quality management system. In the proposed model, fuzzy axiomatic design is selected as a suitable research methodology. The obtained results provide a decision aid for the relevant executives in maritime institutions who design a quality management system integrated with ISO 9001:2015 guidelines.